THE ROLE OF COMPENSATION IN INCREASING TEACHER PERFORMANCE MOTIVATION - Listiani, Feby Eka; Sa'diah, Muslikatus; Aprilia, Rengga; Wulandari, Ayu; Trihantoyo, Syunu (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
This research was conducted to find out how closely the relationship between teacher compensation in the form of salary and teacher performance motivation at BA 'Aisyiyah Kutukuon, Ponorogo. The app oach used in this study is qualitative. The method used in data collection was observation and interviews with five teachers at BA 'Aisyiyah Kutukulon. The results of the analysis obtained are that there are only two types of income earned by teachers in the form of basic salary and allowances which are obtained twice in one year. The low salary of private teachers is suspected of having a relationship between their earnings and performance motivation. On the other hand, after conducting research, the low salary earned did not have a significant impact on the learning system. This is evidenced by the teacher's ability to plan lessons and implement learning at BA 'Aisyiyah Kutukulon. Thus, it can be concluded that the role of income earned does not have a significant impact on decreasing performance motivation